KONSTRUKSI PEMIKIRAN PROFESOR YUSNY SABY DALAM MENGATASI RADIKALISME DAN EKSTREMISME - Syamsul Bahri; Sri Suyanta (Kalam: Jurnal Agama dan Sosial Humaniora, 2024)
This article discusses Prof. Yusny Saby's thoughts on strategies and practices in reducing radicalism and extremism. The research employs a qualitative approach with a descriptive exploratory method. Data were collected through in-depth interviews and observations. Data analysis techniques include grouping information, coding emerging themes, and developing descriptive narratives to comprehensively depict the informant's views and contributions. The findings indicate that Prof. Yusny's understanding encompasses several key aspects: 1) Religious Cosmology: Prof. Yusny emphasizes human responsibility as God's stewards on earth, with Pancasila as the microcosm of religious values. 2)Terrorism and Jihad: Terrorism contradicts Islamic teachings of rahmatan lil’alamin, and jihad should include sincere efforts like seeking knowledge and upholding justice, not merely physical warfare. 3)Musyawarah and Democracy: The concept of musyawarah in Islam aligns with democratic principles, and leaders should be chosen based on expertise and understanding. 4) Public Services and Law Enforcement: Addressing terrorism in Indonesia must focus on justice in public services and law enforcement to prevent dissatisfaction that triggers radicalism. 5) Humane Approach and Ulama Certification: A humane approach and guidance involving idol figures from extremist circles, as well as ulama certification, are necessary to ensure the correct delivery of religious teachings.